Avaliação da aplicação de compósitos poliméricos em engrenagens cônicas de transmissão de máquinas agrícolas - Melegari, Luis Fernando (2017)
The use of polymeric materials to substitute an array of others like metal has its development level increased when new compounds are applied as well as new formation technologies. An approach of the main factors lately used for its assessment was necessary to prove the polymeric material’s behavior when applied in gears for strength transmission. The presented analysis were based on practical experiences and through methods of finite elements, using diverse composites and addition loads to form the tested polymers in controlled conditions for torque, temperature and rotation, making use of the device development of movement and specific control. The polymeric gears behave in different ways according to specific conditions of temperature, rotation and torque request, presenting a variety of results due to the polymers used in its formation. The geometry of the project and the profile construction of the conical gears’ tooth had direct influence under the performance, being possible to reduce the tensions in the tooth’s root. The injected pieces supply a body of proves to a mechanic dynamic thermal analysis, these results present discrepancy among the base materials regarding Tm. The replacement of metallic materials for polymeric materials must consider the characteristics of each application.